Physiological responses of young vegetative quinoa (Chenopodium quinoa Willd.) leaves to high temperatures under controlled conditions - Fishbein, Talya; Matityahu, Ifat; Bertero, Daniel; Rubinovich, Lior (Frontiers in Plant Science, 2026)
Global warming is increasing the frequency of extreme heat events, posing major challenges for crop productivity and food security. Young vegetative quinoa (YVQ; Chenopodium quinoa Willd.) has emerged as a promising high-protein leafy crop, but little is known about its physiological performance under very high temperatures. This study examined the short-term responses of YVQ (cv. Peppermint) to a series of high-temperature gradients (30–55°C) under controlled conditions: 30-day-old plants were exposed to high temperatures for 5 days and evaluated before exposure, and 1 day (After 1d) and 14 days (After 14d) after exposure to assess their recovery. Despite exposure to peak temperatures of 55°C, no visible foliar injury was observed. Maximum quantum yield of photosystem II (Fv/Fm) remained stable across treatments, indicating protection of the photosynthetic apparatus. Leaf chlorophyll content index (CCI) increased at 40–49°C but plateaued at 55°C. In contrast, CO2 assimilation (A) and stomatal conductance (gs) declined sharply above 43°C but recovered at 43–49°C After 14d, suggesting transient impairment followed by acclimation. Exposure to 55°C resulted in a significant and non-recoverable reduction in gas-exchange parameters. Electrolyte leakage decreased at 43–46°C but increased markedly at 52–55°C, indicating a shift from stress priming to irreversible membrane injury. Total protein content reached its maximum following exposure to 55°C, likely reflecting accumulation of stress-induced proteins. Strong correlations were found between temperature and A, gs, electrolyte leakage, and CCI After 1d, but not After 14d. Temperature was also positively correlated to protein content After 14d. Overall, our findings suggest that temperatures of 43–49°C activated protective adaptation mechanisms, but temperatures ≥52°C exceeded compensatory capacity and caused irreversible impairment of carbon assimilation and membrane integrity. These findings demonstrate remarkable thermotolerance of YVQ and highlight its potential as a climate-resilient leafy crop for future hot environments.